Reasons for COVID-19 vaccine hesitancy in ethnic minority groups: A systematic review and thematic synthesis of initial attitudes in qualitative research - Christina Shearn; Eva M. Krockow (Elsevier, 2023)
Despite being disproportionately affected by the COVID-19 pandemic, ethnic and racial minority groups show widespread vaccine hesitancy. Adherence to ongoing booster vaccine campaigns is required to contain future spread of the virus and protect health systems. This review aims to appraise and synthesise qualitative studies published from December 2021 to February 2022 addressing the issue for an in-depth exploration of initial COVID-19 vaccine hesitancy in minorities, including refugee, asylum seeker and migrant populations. A systematic literature search of five databases identified 15 eligible studies. Thematic synthesis identified three main themes of "institutional mistrust", "lack of confidence in vaccine and vaccine development process", and "lack of reliable information or messengers". Two minor themes included "complacency/perceived lack of need" and "structural barriers to vaccine access". "Institutional mistrust" permeated several other themes, demonstrating the need for culturally sensitive approaches. Applying our findings to the World Health Organisation's Three C Model of vaccine hesitancy, the "confidence" dimension appears to represent a disproportionately large barrier to vaccine uptake in ethnic minority groups. Indeed, nuanced adaptations of the model may be necessary to explain vaccine hesitancy in those groups. Further research is required to explore factors facilitating vaccine uptake to monitor changes in hesitancy over time.